A study on two sets of packaging conditions for pork chops - Pascual, Loreto R.; De Leon, Sonia Y. (1967)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Meat -- Packaging